Trinity & beyond the atomic bomb movie - Kuran, Peter; Munro, Alan, 1958-; Narrie, Scott; Pugsley, Don; Shatner, William; Stromberg, William T.; Marian, Barbu; Moskovskii simfonicheskii orkestr; Visual Concept Entertainment (Firm); Documentary Film Works (Firm) (Santa Clarita, CA Visual Concept Entertainment, 2006)
"[C]hronicles the top secret, strange and visually compelling history of the design, production and testing of atomic and hydrogen bombs by the United States. In addition to uncovering rare film from top-secret government archives, [director] Kuran traveled far and wide to obtain startling footage of nuclear tests conducted by China, plus the largest atomic explosion ever detonated by Russia."--Container.
Originally produced in 1995.
Special features: Slide show ; Atomic bomb tests in 3-D ; Unedited bomb explosion ; Atomic bomb footage ; biographies of Edward Teller, Frank H. Shelton, director Peter Kuran, and composer William Stromberg [text feature] ; 50th anniversary trailer ; complete list of all nuclear detonations by the US, including yields [PDF document, DVD-ROM feature] ; atomic trailers [theatrical trailers of other nuclear bomb-related films].
Director of photography, Barbu Marian ; music composed and conducted by William Stromberg ; music performed by the Moscow Symphony Orchestra ; editorial supervisor, Jo Martin.
Narrated by William Shatner ; includes interviews with Dr. Edward Teller, Dr. Frank H. Shelton.
DVD-ROM ; widescreen presentation ; Dolby Digital 5.1 Surround sound ; access to DVD-ROM special features requires computer with DVD-ROM drive.
109161
Keywords: Teller, Edward, -- 1908-2003 -- Interviews; Shelton, Frank H. -- 1924-2014 -- Interviews; 1946; Atomic bomb -- History; Hydrogen bomb -- History; Atomic bomb -- Testing -- History; Operation Crossroads, Marshall Islands, 1946.; Nuclear weapons -- Testing -- History; Documentary films; Feature films; Historical films; History; Interviews; Nonfiction films